The levels of vitamins A, E, B12 and folic acid in noise-induced hearing loss - Gök, Uzeyir; Halifeoglu, Ihsan; Yildiz, Mücahit (My University, 2004)
OBJECTIVES: To investigate the levels of vitamin A, E, B12, folic acid in employees with hearing loss due to noise. PATIENTS AND METHODS: Employees in a local hydroelectric powerhouse who suffered from hearing loss due to noise were included in the study. Study and control groups were composed of 28 employees (mean age 37+/-5 years) and 30 voluntary subjects (mean age 36+/-4 years), respectively. All the subjects in patient and control groups were males. Blood samples were obtained from all subjects and vitamin A, E, B12 and folic acid levels were measured. RESULTS: Level of vitamin B12 was found low in the patient group and normal in the control group and these were found statistically significant (p<0.005). There were no significant differences between vitamin A, E and folic acid levels. CONCLUSION: We think that measurement of vitamin B12 in routine control of the people who are working in noisy environment may be useful.
Gürültüye bagli işitme kayipli hastalarda vitamin A, E, B12 ve folik asit düzeyleri.
Keywords: Adult; Case-Control Studies; Female; Folic Acid; Hearing Loss, Noise-Induced; Humans; Male; Middle Aged; Occupational Diseases; Vitamin A; Vitamin B 12; Vitamin E; alpha tocopherol; cyanocobalamin; folic acid; retinol; adult; article; blood; case control study; female; human; male; middle aged; noise injury; occupational disease